A STUDY OF PHOSPHATE ION RELEASE FROM GLASS-IONOMER DENTAL CEMENTS - Kunle Awosanya; John W. Nicholson (Ceramics-Silikáty, 2014)

(untitled)
Phosphorus elution from four commercial brands of glass-ionomer dental cement has been studied. Release was found to be linear with time up to 14 days in both neutral and acid conditions, indicating that release occurs by dissolution rather than by diffusion. Release was substantially greater in acidic conditions than neutral ones. The species released were studied by ion chromatography, and all brands showed clear release of the monomeric species orthophosphate PO4 3-. Attempts to confirm this using 31P NMR spectroscopy were generally unsuccessful due to the relatively high detection limit in NMR, but for the neutral solution derived from the brand Chemflex, a weak signal was observed at 1.64 ppm, which confirmed the occurrence of orthophosphate. In addition, an unidentified species was released by all brands except Fuji IX, and this has been tentatively identified as mono-fluorophosphate PO3F2-. It is suggested that the release of these phosphate species may be beneficial in promoting remineralization when these cements are used clinically